2010
DOI: 10.1111/j.1442-2042.2010.02672.x
|View full text |Cite
|
Sign up to set email alerts
|

Micropapillary urothelial carcinoma of the urinary bladder: A clinicopathological analysis of 24 cases

Abstract: Objectives: To stratify patients with micropapillary urothelial carcinoma of the urinary bladder based on the percentage of micropapillary component and to correlate tumor volume with other clinicopathological features. Methods: Cases of micropapillary urothelial carcinoma of the urinary bladder from 2002 to 2009 were identified. Only patients with available follow-up information were included in the analysis. Tumor volumes were stratified based on the percentage of micropapillary component (<50%, >50% and 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 23 publications
0
10
1
Order By: Relevance
“…4 The proportion of MPUC appears to predict poor prognosis, [12][13][14] and at least predicts high pathologic stage and lymph node metastasis. 4,5 Multiple authors 4,5,12 recommend a quantitative report of MPUC whenever it is present.…”
Section: Immunohistochemical Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 The proportion of MPUC appears to predict poor prognosis, [12][13][14] and at least predicts high pathologic stage and lymph node metastasis. 4,5 Multiple authors 4,5,12 recommend a quantitative report of MPUC whenever it is present.…”
Section: Immunohistochemical Findingsmentioning
confidence: 99%
“…Micropapillary urothelial carcinoma occurs almost exclusively in the setting of conventional UC, 2,3 and the proportion of MPUC predicts high pathologic stage and lymph node metastasis. 4,5 The overall prognosis is poor; the 5-year and 10-year survival in the largest study were 51% and 24%, respectively. …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Several studies demonstrated that micropapillary urothelial carcinoma is diagnosed at a more advanced stage, and is associated with adverse outcome relative to typical urothelial carcinoma. [4][5][6][7][8] However, a recent study found that, although patients with micropapillary urothelial carcinoma presented at higher stage than patients with typical urothelial carcinoma, the outcomes following radical cystectomy were no different when matched for stage and other clinicopathologic variables. 9 In addition to unique histologic features, studies have shown that micropapillary urothelial carcinoma exhibits amplification of the human epidermal growth factor receptor (ERBB2 or HER2) in over 40% of cases.…”
mentioning
confidence: 99%
“…Most cases of urothelial MPC are associated with conventional areas of transitional cell carcinoma, and it is still not clear what percentage of micropapillary growth correlates with a poor outcome. Some authors consider that this term should be reserved for those tumors showing >50% of micropapillary growth [7], while others recommend that even a focal presence is sufficient to constitute MPC and should be mentioned in the report since it shows a more aggressive behavior [4,8]. …”
Section: Introductionmentioning
confidence: 99%